Development of 3D Digital Animation-Based Basketball Shooting Training for Amateur Athletes - Ali Munir (Universitas Muhammadiyah Enrekang, 2025)
The process of developing the talent of an athlete needs to be carried out from an early age. Therefore, coaches are required to design various training modification media according to age classification. One of them is to utilize technology media based on 3D digital animation video. This research aims to determine the validity and reliability values of the training media and the effectiveness of the training program media named animals, based on 3D digital animation, to improve free throw shooting in amateur class athletes. The population in this study consists of 40 amateur athletes, and the sampling method used is Total Sampling, resulting in a sample size of 40 athletes. In addition, this study involved 7 validators from disciplines that support this research. Before the data was analyzed, preliminary tests were conducted for analysis requirements, namely normality tests and homogeneity tests. Data analysis was performed using t-tests for paired data comparisons using SPSS version 26. The results of this study show that the validity value is 0.864 and the reliability is 0.980 > 0.05. This indicates that the media product for practicing animal names based on 3D digital animation is valid and reliable. In addition, the product's results are effective after being implemented to amateur class athletes, where the effectiveness test using the Paired Sample T-Test found a Sig. (2-tailed) value of 0.000. Based on these research results, it can be concluded that the 3D digital animation-based training media product shows positive, valid, and reliable results. Therefore, this product becomes a solution for coaches in providing training, especially for amateur athletes in executing Free Throw shooting techniques in basketball